ANALYSIS OF THE "SOME" MODEL (SHARE, OPTIMIZE, MANAGE, ENGAGE) INSTAGRAM ACCOUNT @tnlkep Kepulauanseribu IN THE FRAMEWORK OF DIGITAL PROMOTION OF A THOUSAND ISLANDS MARINE PARK AS AN ECO-TOURISM DESTINATION FOR THE MILLENIAL GENERATION - Yunita Sari; Mediana Handayani (Moestopo International Review on Social, Humanities, and Sciences, 2021)
The fact that millennial generation is the breadwinner of the Indonesian economy cannot be ignored by the government and tourism industry businesses. The Thousand Islands Marine National Park seeks to use Instagram social media to attract potential tourists from millennial groups. A total of 110 @tnlkepulauaneribu uploads were then analyzed with descriptive qualitative research methods to find out how Gina Lutrell's SOME (Sharring, Optimize, Manage, Engagement) Model was used in managing the Instagram account communication @tnlkep Kepulauan Seribu as an effort to digitally promote the Thousand Islands National Park as an Ecotourism Destination for Generations Millennial. The results of this study indicate that the manager of the @tnlkepulauanseribu account has not implemented The Circular Model of SOME to the fullest. The engagement process (is the process that is at least maximally carried out. This can be seen from the lack of adequate engagement to nurture and create new followers. There are not many communication activities that can have a binding impact on followers and prospective followers of the @tnlkepulauanseribu account.